Transforming growth factor β activated kinase 1: a potential therapeutic target for rheumatic diseases. (17th August 2016) - Fechtner, Sabrina; Fox, David A.; Ahmed, Salahuddin
Abstract: Pro-inflammatory cytokines such as IL-1β, IL-6 and TNF-α are central regulators of autoinflammatory diseases. While targeting these cytokines has proven to be a successful clinical strategy, the long-term challenges such as drug resistance, lack of efficacy and poor clinical outcomes in some patients are some of the limitations faced by these therapies. This has ignited strategies to reduce inflammation by potentially targeting a variety of molecules, including cell surface receptors, signalling proteins and/or transcription factors to minimize cytokine-induced inflammation and tissue injury. In this regard, transforming growth factor β activated kinase 1 (TAK1) is activated in the inflammatory signal transduction pathways in response to IL-1β, TNF-α or toll-like receptor stimulation. Because of its ideal position upstream of mitogen-activated protein kinases and the IκB kinase complex in signalling cascades, targeting TAK1 may be an attractive strategy for treating diseases characterized by chronic inflammation. Here, we discuss the emerging role of TAK1 in mediating the IL-1β, TNF-α and toll-like receptor mediated inflammatory responses in diseases such as RA, OA, gout and SS. We also review evidence suggesting that TAK1 inhibition may have potential therapeutic value. Finally, we focus on the current status of the development of TAK1 inhibitors and suggest further opportunities for testing TAK1 inhibitors in rheumatic diseases.